Coupling Kinetic Modelling with SAOS and LAOS Rheology of Poly(n‐butyl acrylate). Issue 12 (21st June 2022) - Grotian genannt Klages, Hannah; Ermis, Nihal; Luinstra, Gerrit Albert; Zentel, Kristina Maria
Abstract : Front Cover : The interplay between reaction conditions of the polymerization process of n‐butyl acrylate with the resulting product properties is investigated and quantified in article number 2100620 by Kristina Maria Zentel and co‐workers. A detailed kinetic model for the polymerization is validated against model experiments and used to determine the polymeric microstructure—here molar mass distribution and branching densities. They can be directly linked to the rheological behavior in the linear (SAOS) as well as non‐linear regime (LAOS).